Accelerated Degradation Behavior and Cytocompatibility of Pure Iron Treated with Sandblasting - Zhou, Juncen; Yang, Yuyun; Alonso Frank, Micael; Detsch, Rainer; Boccaccini, Aldo R.; Virtanen, Sannakaisa (ACS Applied Materials and Interfaces, 2016)
Fe-based materials are of interest for use in biodegradable implants. However, their corrosion rate in the biological environment may be too slow for the targeted applications. In this work, sandblasting is applied as a successful surface treatment for increasing the degradation rate of pure iron in simulated body fluid. Two sandblasting surfaces with different roughness present various surface morphologies but similar degradation products. Electrochemistry tests revealed that sandblasted samples have a higher corrosion rate compared to that of bare iron, and even more noteworthy, the degradation rate of sandblasted samples remains significantly higher during long-term immersion tests. On the basis of our experimental results, the most plausible reasons behind the fast degradation rate are the special properties of sandblasted surfaces, including the change of surface composition (for the early stage), high roughness (occluded surface sites), and high density of dislocations. Furthermore, the cytocompatibility was studied on sandblasting surfaces using human osteoblast-like cells (MG-63) by indirect and direct contact methods. Results revealed that sandblasting treatment brings no adverse effect to the growth of MG-63 cells. This work demonstrates the significant potential of sandblasting for controlling the degradation behavior of iron-based materials for biomedical applications

A facile and scalable method to produce superhydrophic stainless steel surface - Alonso Frank, Micael; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Applied Surface Science, 2014)

A novel local drug delivery system: Superhydrophobic titanium oxide nanotube arrays serve as the drug reservoir and ultrasonication functions as the drug release trigger - Zhou, Juncen; Alonso Frank, Micael; Yang, Yuyun; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Materials Science and Engineering C, 2018)

Functionalization of steel surfaces with organic acids: Influence on wetting and corrosion behavior - Alonso Frank, Micael; Meltzer, Christian; Braunschweig, Björn; Peukert, Wolfgang; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Applied Surface Science, 2017)
Self-assembled monolayers (SAMs) have been used to tailor surface properties of different metal surfaces. Typically SAMs can be bound to surface hydroxyls of a thin oxide layer that forms on the surface of a less noble metal and dominates its properties. The effects of SAMs with different anchoring groups and chain lengths regarding wettability, corrosion resistance and homogeneity of the layer were studied in detail. Alkyl carbonic and phosphonic acids were selected to create a hydrophobic layer on the surface of stainless steel ASIS 316L and on carbon steel N80. SAMs were formed by dip-coating of the samples in an organic acid ethanolic solution. Sum frequency generation (SFG) analysis together with contact angle and electrochemical measurements were carried out to explore correlations between tailored wettability, corrosion resistance, and layer homogeneity on one side, and the chain length, anchor group, concentration and immersion time on the other side. The homogeneity of the layers as well as the resulting surface hydrophobicity increased with an increase of the immersion time, the contact angle reached a maximum (ca. 120°) for an immersion time of approximately 2 days.
Keywords: Carbon steel N80; Hydrophobicity; Myristic acid; Octadecylphosphonic acid (ODPA); Stainless steel 316 L; Stearic acid; Sum frequency generation; Surface functionalization